Can T Tauri stars produce high-energy radiation? - del Valle, Maria Victoria (2010)
T Tauri stars are low mass, pre-main sequencestars. These objects are surrounded by an accretion disk and present strongmagnetic activity. T Tauri stars are copious X-rays emitters. The X-rays arelikely generated by powerful magnetic reconnection events.Strong shocks  can be produced by  massive reconnection in the stellar magnetosphere. These shocks or the reconnection of the field might accelerate particles up to relativistic energies, as observed in the Sun.We present a model for the high-energy radiation produced in themagnetosphere of T Tauri stars. We discuss whether this emission isdetectable with the existing gamma-ray telescopes.